If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 5) * x = 36 Reorder the terms: (5 + x) * x = 36 Reorder the terms for easier multiplication: x(5 + x) = 36 (5 * x + x * x) = 36 (5x + x2) = 36 Solving 5x + x2 = 36 Solving for variable 'x'. Reorder the terms: -36 + 5x + x2 = 36 + -36 Combine like terms: 36 + -36 = 0 -36 + 5x + x2 = 0 Factor a trinomial. (-9 + -1x)(4 + -1x) = 0Subproblem 1
Set the factor '(-9 + -1x)' equal to zero and attempt to solve: Simplifying -9 + -1x = 0 Solving -9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -1x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = 0 + 9 -1x = 0 + 9 Combine like terms: 0 + 9 = 9 -1x = 9 Divide each side by '-1'. x = -9 Simplifying x = -9Subproblem 2
Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4Solution
x = {-9, 4}
| 2(x-4)+x*x=4-(x+2)*(3-x) | | y+2(y-8)= | | 29/66/e^50 | | (X+4)(x-15)-6x=0 | | 15+18-16=13 | | 2x^4=9x^2 | | 5y-8x-10=0 | | e^50*k=29/66 | | (2y-6)+(30)+(x)=180 | | (x-8)2=0 | | (-3/4)/(-5/6) | | -3x-2(-7x-4)=74 | | 13=-4(x+8)+5x | | (7t-2)-(-3t+1)=(1-3t) | | -9/-5= | | 5-3(2h+6)=7+5h | | (4x-3)(8x+4)=0 | | 3(x+2)+3x+1=2(x-1)-7 | | 11/28=4/x | | 12x^3-3x^2=0 | | 3.5/x=11/28 | | 55x-12=x-24 | | 59+1.75x=39.99+2.50x | | x(1M)+(-2N)=0 | | 2/3x2-5= | | 3p+6=78 | | 2/3x-5=-2 | | C(t)=2x+180 | | 5x-5y+7a= | | 3=-3/2(x+6) | | Ic(t)=2x+180 | | 16=4(2x+1) |